2020
DOI: 10.23736/s0022-4707.20.10322-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbohydrate and protein co-ingestion during short-term moderate-intensity exercise on cognitive function

Abstract: BACKGROUND: This study aimed to investigate the effects of isocaloric Carbohydrateelectrolyte solution (CES) and Carbohydrates-electrolyte-protein solution (CEPS) consumed during moderate-intensity exercise on cognitive function. METHODS: 23 healthy participants (age: 21.71.5 years, body mass index: 21.82.0 kg/m 2 , and peak oxygen consumption (VO2peak): 42.46.9 ml/kg/min) were recruited in the study. Participants completed two main experiment trials using a cross-over study design. In each trial, they comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Our research showed a significantly negative linear relation between total protein intake and the mean and maximal speed threshold in cognitive testing. Previous investigations reporting a positive relationship between dietary protein consumption and cognitive response were conducted in aging persons, which often consume less protein than the needed protein for maintaining their health (37,38). However, our population was younger, and many consumed above the RDA for protein, which may have influenced the conflict with the present result.…”
Section: Discussionmentioning
confidence: 65%
“…Our research showed a significantly negative linear relation between total protein intake and the mean and maximal speed threshold in cognitive testing. Previous investigations reporting a positive relationship between dietary protein consumption and cognitive response were conducted in aging persons, which often consume less protein than the needed protein for maintaining their health (37,38). However, our population was younger, and many consumed above the RDA for protein, which may have influenced the conflict with the present result.…”
Section: Discussionmentioning
confidence: 65%
“…The brain is very demanding in terms of energy metabolism [40]. Its functions, such as cognitive learning, memory and thinking, are interlinked to the efficient utilization of glucose [41,42]. Red blood cells and neurons have a big energy demand too [43].…”
Section: Resultsmentioning
confidence: 99%